Relationship Between BMI, Dietary and Lifestyle Characteristics and the Severity of Acne vulgaris - Al-Hattab, Mohammed K.; Jameel Abbass , Zahraa; Ahmed Fakhry , Fatin; H. Sahib , Nadia (Hammurabi Journal of Medical Sciences, 2024)
Background: Acne is believed to impact around 9.4% of the global population, positioning it as the eighth most widespread condition on the globe. Objectives: to assess if BMI (among other risk variables) has an influence on severity of acne vulgaris. Material and Methods: This is a cross-sectional study that included 120 patients and was conducted at dermatology clinic from the 3rd of May 2023 to the 3rd of March 2024. A total of 120 patients were included. Patients sociodemographic characteristics were recorded (age and sex), as well as BMI and the following information: age of onset, smoking, excessive consumption of sweets, milk or dairy products, fats, spices, the presence of psychological stress, family history of acne, and the daily duration of sunlight exposure. All the patients were thoroughly examined by the attending dermatologist and the acne was graded into mild, moderate, and severe. Results: Statistical analysis revealed no significant association between the severity of acne and BMI. Furthermore, no significant association was found between the severity of acne and each of the following risk factors: smoking, cosmetic, milk or diary consumption, spicy diet, fatty diet and family history. Whereas higher severity was significantly associated with increased sugar consumption, stress, and more hours of sunlight exposure. Conclusion: Based on the findings of the present study, BMI was not significantly associated with the severity of acne vulgaris. Among other dietary and lifestyle characteristics, sugar consumption, stress, and increased exposure to sunlight were predictors of severity. However, larger population sized studies are essential to validate these findings.